2021
DOI: 10.1109/tbcas.2021.3108725
|View full text |Cite
|
Sign up to set email alerts
|

A 32-Channel Time-Multiplexed Artifact-Aware Neural Recording System

Abstract: This paper presents a low-power, low-noise microsystem for the recording of neural local field potentials or intracranial electroencephalographic signals. It features 32 timemultiplexed channels at the electrode interface and offers the possibility to spatially delta encode data to take advantage of the large correlation of signals captured from nearby channels. The circuit also implements a mixed-signal voltage-triggered autoranging algorithm which allows to attenuate large interferers in digital domain while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The PEF can be calculated as And the PEF of the amplifier is calculated to be 10.17. Figure 11 [6,7,9,13,[15][16][17][20][21][22][23][24][25][26][27][28][29][30][31] shows the input-referred noise versus the supply current of the amplifier. The proposed work features a low input-referred noise while achieving a competitive NEF.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The PEF can be calculated as And the PEF of the amplifier is calculated to be 10.17. Figure 11 [6,7,9,13,[15][16][17][20][21][22][23][24][25][26][27][28][29][30][31] shows the input-referred noise versus the supply current of the amplifier. The proposed work features a low input-referred noise while achieving a competitive NEF.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Since the placement of the individual channels in the connector to the head stage does not seem to explain the cross-talk Figure S2, the circuitry inside the headstage is our primary suspect for cross-talk. There the analog signals from many channels are simultaneously amplified, filtered and converted to digital; steps known to be very sensitive to cross-talk (Pérez-Prieto & Delgado-Restituto, 2021; Perez-Prieto et al, 2021). Indeed, in the case of macaque Y, previous recordings had used the analog signal processing headstage ‘Samtec’ and ‘Patientcable’ (Blackrock Microsystems) (Riehle et al, 2013; Brochier et al, 2018), and after updating it to ‘Cereplex E’ (Blackrock Microsystems) we observed far fewer artifacts, likely due to the improved insulation and circuit design.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been suggested to remove the synchrofacts from neural recordings. Hardware implementations can avoid cross-talk by improving the isolation and design of the circuits (Blot & Barbour, 2014; Nelson et al, 2017; Pérez-Prieto & Delgado-Restituto, 2021; Perez-Prieto et al, 2021). Most neuroscientists do not design their own custom hardware, and hence have to use post-hoc methods to remove the synchrofacts from their data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(b) could significantly reduce the number of amplifiers and ADCs. Similar recording architectures are also explored in [7], [8]. This multiplexing technique can also be co-designed with direct digitalization converters explained in the following sections.…”
Section: Neural Recording System Architecturementioning
confidence: 99%